Effectiveness of different irrigation systems on smear layer removal: A scanning electron microscopic study - Ahmetoglu, Fuat (Medknow Publications & Media Pvt Ltd, 2014)
OBJECTIVES: To evaluate effectiveness of the apical negative pressure irrigation (EndoVac), passive ultrasonic irrigation (PUI), and conventional needle irrigation (CI) systems on smear layer (SR) removal. MATERIALS AND METHODS: Sixty single-rooted canines were prepared using NiTi rotary files and subjected to different irrigation regimens: EndoVac with NaOCl (Group 1) or NaOCl/EDTA (Group 2); PUI with NaOCl (Group 3) or NaOCl/EDTA (Group 4); CI with NaOCl (Group 5) or NaOCl/EDTA (Group 6). The roots were split longitudinally. SEM images were taken to evaluate the amount of residual SR. RESULTS: In Groups 1, 3, and 5, there was no removal of SR (P > 0.05). The coronal thirds within Groups 2, 4, and 6 were cleaned completely, but the middle and the apical thirds was achieved partially or completely (P > 0.05). CONCLUSION: Regardless of which irrigation system was used, the use of NaOCl alone failed to remove the SR. In NaOCl/EDTA combination groups, the SR was removed partially or completely and no statistical significance. This study demonstrated that in order to remove the SR should be used EDTA solution for final irrigation in the root canal, regardless of the technique in each of the three.